A pentacarbomethoxycyclopentadiene (PCCP) organic Brønsted acid catalyzed stereoselective glycosidation of N-pentenyl orthoesters (NPOE) of d-glucose and d-galactose, in conjunction with N-iodosuccinimide. (December 2022) - Aswathy, Maniyamma; Abhijith, Balan; Lankalapalli, Ravi S.; Radhakrishnan, Kokkuvayil V.
Abstract: Herein, we report our preliminary results in utilizing the organic Brønsted acid, pentacarbomethoxycyclopentadiene (PCCP), for catalysing the glycosidation with n -pentenyl orthoesters (NPOE) of d -glucose and d -galactose in the presence of N -iodosuccinimide (NIS). Benzoyl and benzyl protection in d -glucosyl NPOEs led to 1, 2-trans glycosides, while acetyl protection in NPOE led to a mixture of 1, 2-cis and trans glycosides with >75% cis selectivity, and d -galactosyl NPOEs led to 1, 2-orthoesters. Substrate scope was demonstrated with acceptors of natural product relevance. This article highlights the prospect of utilizing the organic Brønsted acid, PCCP, for stereoselective glycosidation. Graphical abstract: Image 1 Highlights: A pentacarbomethoxycyclopentadiene (PCCP), organic Brønsted acid, catalyzed glycosidation. Stereoselective glycosidation of N -pentenyl orthoesters (NPOE) with PCCP catalyst in conjunction with N -iodosuccinimide. Benzoyl and benzyl protection in d -glucosyl NPOEs led to 1, 2-trans glycosides. Substrate scope was demonstrated with aglycones of natural product relevance.